Vocabulary Learning Strategies of Turkish EFL Learners: A Focus on Gender - Okyar, Hatice (JET (Journal of English Teaching), 2021)
This study aimed to (a) identify vocabulary learning strategies (VLSs) employed by Turkish EFL learners; (b) determine whether the use of VLSs varies by gender. To achieve these aims, the vocabulary learning strategies scale developed by Kocaman and Kizilkaya Cumaoglu (2014) was administered to preparatory school students (n=209) at a state university in Turkey. Descriptive statistics (means, standard deviations) and an independent-samples t-test were used for statistical analyses. The results revealed that the frequency of VLS use was at a medium level. In addition, analysis of the sub-dimensions of the scale showed that memory, cognitive, compensation, and social strategies were used at a medium frequency level, while metacognitive and affective strategies were used at a high frequency. When VLS use was analyzed with respect to gender, a significant difference was seen between males and females, with female students having a higher total mean score than male students. Also, female students reported more use of memory, cognitive, compensation, metacognitive, and affective strategies; however, no statistically significant gender difference was found regarding the frequency of the use of social strategies.